Interpersonal Communication of Persons with Visual Impairments: Its Influence on Self-Concept and Resilience among Members of the Indonesian Blind Association Community in Medan City, Indonesia - Nurhayati Nurhayati; Iskandar Zulkarnain; Humaizi Humaizi (Department of Social Studies Education, Faculty of Tarbiyah and Teacher Training, Datokarama State Islamic University of Palu, Central Sulawesi, Indonesia., 2026)
Loss of vision after birth requires individuals to make psychological and social adjustments so that interpersonal communication becomes a factor that has the potential to support the formation of self-concept and resilience. This study aims to analyze the influence of interpersonal communication on the self-concept and resilience of people with non-congenital visual impairments among members of the Indonesian Blind Association (PERTUNI) in Medan City. The study used a quantitative approach with a correlational method. The study population was 120 members of PERTUNI in Medan City and all of them were sampled through a total sampling technique. Data were collected using a questionnaire that was read directly to respondents and analyzed using SPSS version 27. The results showed that interpersonal communication had a positive and significant effect on self-concept (β = 0.210; t = 2.936; p = 0.004) with a coefficient of determination of 0.068, which means it explains 6.8% of the variation in self-concept. Interpersonal communication also had a positive and significant effect on resilience (β = 0.384; t = 3.829; p = 0.001) with a coefficient of determination of 0.111 or explaining 11.1% of the variation in resilience. This finding indicates that interpersonal communication contributes to the formation of self-concept and resilience in people with non-congenital visual impairments.